The molecular basis of MeCP2 function in the brain - Tillotson, R; Bird, A (Elsevier, 2019)
MeCP2 is a reader of the DNA methylome that occupies a large proportion of the genome due to its high abundance and the frequency of its target sites. It has been the subject of extensive study because of its link with 'MECP2-related disorders', of which Rett syndrome is the most prevalent. This review integrates evidence from patient mutation data with results of experimental studies using mouse models, cell lines and in vitro systems to critically evaluate our understanding of MeCP2 protein function. Recent evidence challenges the idea that MeCP2 is a multifunctional hub that integrates diverse processes to underpin neuronal function, suggesting instead that its primary role is to recruit the NCoR1/2 co-repressor complex to methylated sites in the genome, leading to dampening of gene expression.